Expression status of PD‐L1 and B7‐H3 in mesothelioma. Issue 12 (7th October 2020) - Matsumura, Eiji; Kajino, Kazunori; Abe, Masaaki; Ohtsuji, Naomi; Saeki, Harumi; Hlaing, May Thinzar; Hino, Okio
Abstract : Mesothelioma is a rare, aggressive malignancy with poor outcome, and has limited treatment options. The aim of this study was to perform a comprehensive analysis of programmed death ligand 1 (PD‐L1) and B7 homolog 3 (B7‐H3) expression in mesothelioma. We investigated the protein expression of PD‐L1 and B7‐H3 and their potential correlation with histological subtype, which might help to develop new therapies targeting these immune checkpoint molecules. Expression analysis of PD‐L1 and B7‐H3 was performed by immunohistochemistry using serial tissue sections of specimens obtained from 31 patients with mesothelioma. Tumors were classified into 22 epithelioid, 6 sarcomatoid, and 3 biphasic types. Of the 31 patients, 13 (41.9%) were positive for PD‐L1 and 28 (90.3%) were B7‐H3 positive. Twelve of the 13 PD‐L1 positive patients were positive for B7‐H3. PD‐L1 and B7‐H3 were widely co‐expressed in biphasic and sarcomatoid type tumor cells. These findings might provide a rationale for the use of combination therapy for mesothelioma by targeting PD‐L1 and B7‐H3, as well as the development of anti‐B7‐H3 or anti‐PD‐L1 single agents.